(untitled) (Research, Society and Development, 2024)
Dravet syndrome is a severe epileptic encephalopathy that manifests in early childhood and is characterized by hemiclonic or tonic-clonic seizures. One of the non-pharmacological treatment options for this condition is the ketogenic diet, which aims to induce ketosis in the body. This diet is widely recognized as a complementary therapy in the management of patients with epilepsy that is resistant to conventional medications. The present study aimed to evaluate the therapeutic role of the ketogenic diet in patients with Dravet syndrome, focusing on its efficacy as an adjunct therapy, diet tolerability, and the main reported adverse effects. For this, a bibliographic search was conducted in the PubMed database through a systematic literature review, analyzing publications from 2014 to 2024 in Portuguese and English. Based on the analyzed data, the use of the ketogenic diet proved to be a promising approach for the treatment of children with Dravet syndrome, demonstrating efficacy in reducing seizure frequency, with adverse effects considered acceptable and good tolerability.